Do negative headlines really undermine the credibility of a quality label? A quasi-natural experiment - Andreas Hildenbrand; Rainer Kühl; Anne Piper (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
In 2013, Stiftung Warentest tested hazelnut chocolate for their leading magazine, called Test. Stiftung Warentest is one of the most important consumer organizations in Germany. Ritter Sport is a high-quality producer of chocolate in Germany. Their hazelnut chocolate did not pass the test. It was given the grade of unsatisfactory. Stiftung Warentest accused Ritter Sport of labelling an artificial flavouring as a natural flavouring. Ritter Sport rejected the accusation. They went to court and won the trial. Stiftung Warentest had to withdraw the issue in question of Test magazine. This affair was all over the media in January of 2014. Using the Ritter Sport versus Stiftung Warentest case, we analyse whether negative headlines really undermine the credibility of a quality label by examining Stiftung Warentest and their quality label, also called Test. In addition, we examine what can be done to restore or, more generally, increase the credibility of a quality label. Based on a quasi-natural experiment, we find that the negative headlines on Stiftung Warentest have undermined the credibility of the Test label. We also find that the credibility of the Test label can be increased by providing reference values to the tests, strengthening the independence of Stiftung Warentest, and using laboratory methods in the tests. For the most part, the same holds true for any quality label. – – Im Jahr 2013 testete Stiftung Warentest Nuss-Schokoladen für das Dezember-Heft ihrer Test- Zeitschrift. Stiftung Warentest ist eine der wichtigsten deutschen Verbraucherorganisationen. Ritter Sport ist ein deutscher Schokoladenhersteller, der Schokoladen von guter Qualität produziert. Im Test fiel die Voll-Nuss-Schokolade von Ritter Sport durch: Note "mangelhaft". Begründet wurde die schlechte Note nicht mit schlechter Qualität, sondern mit einer irreführenden Etikettierung. Der Vorwurf lautete, Ritter Sport hätte ein künstliches Aroma als natürliches Aroma bezeichnet. Ritter Sport bestritt dies, ging vor Gericht und gewann den Prozess. Infolgedessen musste Stiftung Warentest das Test-Heft zurückziehen. Dieser Vorfall war im Januar 2014 in allen überregionalen Medien präsent. Stiftung Warentest und ihr Qualitätssigel, das Testsiegel, machten Negativschlagzeilen ...
Keywords: D8; L1; M3; 330; information; product quality; quality label; source credibility